The Different Types of Overtime Work in Nursing and Their Associations With Nurse and Patient Outcomes: A Cross-Sectional Study Protocol - Raouaa Braiki; Christian Rochefort (Science of Nursing and Health Practices)
Introduction: Nurses often work overtime to fill the shortage of nurses, ensure continuity of care or prevent service breakdowns. Some studies show that working overtime has negative impacts on both nurse and patient outcomes, whereas others suggest that overtime has some beneficial outcomes for patients and nurses. Some authors suggest that these conflicting results across studies could be explained by the type of overtime performed by nurses, an aspect that has received scant research attention.